Virtual Tour Of Tjong A Fie Museum As A Heritage Tour In The Midst Of A Pandemic - Elita Putri Sari Rangkuti (Tourism, Hospitality And Culture Insights Journal, 2022)
This research was conducted at the Tjong A Fie Museum. The Tjong A Fie Museum is one of the historical tourist objects in the city of Medan, many tourists want to visit the Tjong A Fie Museum, but because of the pandemic period, tourists are still afraid to travel. This study aims to explain the implementation of the Virtual Tour. as well as knowing the response of tourists who have taken part in the Virtual Tour at the Tjong A Fie Museum as heritage tourism in the midst of a pandemic. The author uses a descriptive method with a qualitative approach. Data collection is carried out through online questionnaires distributed to tourists who have participated in the Virtual Tour and documentation through Zoom Meetings. The population taken in this study is the number of tourists who take part in virtual tour activities through Zoom Meetings, totaling 34 participants. The conclusion in this study is that the implementation of the Tjong A Fie Museum Virtual Tour as a heritage tour in the midst of a pandemic went well where by using the initial guiding technique opening, guiding, then closing. Tourist responses to the Tjong A Fie Museum Virtual Tour as heritage tourism in the midst of a pandemic are very good where tourists can travel without having to come directly to tourist objects, tourists are satisfied with the information provided by the guide when doing Virtual Tours and according to Virtual Tour tourists as well can be a promotional medium